Chicano Masculinity in Alberto Urrea’s The House of Broken Angels - Kasih, E. Ngestirosa Endang Woro; Wiguna, Gusti Nyoman Adiatma; M. Fithtrullah (Southeast Asian Language and Literature Studies, 2025)
The term machismo, originating from Chicano culture, refers to the construction of masculinity among Chicano men. The Chicano identity itself emerged from the migration of Mexicans to the United States, a process that began with the shifting of the border between Mexico and the U.S. This historical context gave rise to a new cultural identity, including a distinctive form of machismo among Chicano men. This study aims to analyze the representation of machismo in Chicano men as depicted in Luis Alberto Urrea’s The House of Broken Angels. To conduct the analysis, the study employs Bacca Zinn’s theory to explore the meaning of machismo in Chicano culture alongside Stuart Hall’s theory of representation. Methodologically, this research applies a descriptive qualitative approach using library research, with data drawn from the novel’s narration and dialogues. The findings suggest that The House of Broken Angels portrays Chicano machismo as rooted in traditional Mexican masculinity while simultaneously reflecting the cultural identity of Chicano men.